Study on multi-objective optimization for nuclear reactor radiation shield design coupling genetic algorithm with paralleling discrete ordinate code - Liu, Bin; Tan, Yi; Jing, Futing; Hu, Guang; Yan, Mingfei (Frontiers in Energy Research, 2022)
An optimization method combining genetic algorithm and the paralleling SN code HYDRA is developed and applied to shielding design of the Savannah reactor. Several approaches are studied to cope with the multi-objective optimization problem, such as the transforming into single-objective optimization approach, non-dominated sorting approach using NSGA-II and the approach of adding constraints on sub-objectives using the NSGA-II algorithm. Comparing with the current design methods, the optimization method developed in this paper show better performance since the HYDRA calculations are free of statistical fluctuations and the searching process is independent of human preferences. The multi-objective optimization approach with constraints on sub-objectives seems to have the best performance. More optimized individuals satisfying the constraints can be obtained and the optimized objectives show best improvements comparing with the initial design.